IMPACT OF Beauveria bassiana BIOINSECTICIDE APPLICATION ON THE PREDATORY ARTHROPOD COMMUNITY ON RATOONING RICE ON THE FRESH SWAMP AREA - Sumini, Sumini; Herlinda, Siti; Irsan, Chandra Irsan (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2015)
Impact of Beauveria bassiana bioinsecticide application on the predatory arthropod community on ratoon rice in the fresh swamp area. The predatory arthropod community in the swamp area ecosystem was affected by the application of pesticides. This study was conducted to observed the effect of application on predatory arthropod comunity on ratooning rice in the fresh swamp area. This research was conducted in September up to November 2013. The predatory arthropods were sampled using nets and pitfall traps. The results showed that the abundance of predatory arthropod in the control plots was higher than in bioinsectiside plots. There were 8 species of predatory arthropods found in the canopy and 7 soil-dwelling species. The most abundant canopy inhabiting was Verenia linearis, and the most abundant soil dwelling predator was Pherosophus occipitalis.